Sonographic Detection of Iatrogenic Carotid Artery Guidewires During Internal Jugular Vein Catheterization - James Moak; Kristen Swann; Matthew Kongkatong; Jakob Ottenhoff; Christopher Thom (CINQUILL Medical Publishers Inc., 2024)
Background: Visualization of the guidewire during internal jugular (IJ) vein catheterization by point of care ultrasound (POCUS) has been recommended for avoiding inadvertent carotid artery dilation. The purpose of this study was to determine the accuracy of POCUS for identifying guidewires inappropriately placed in the carotid artery. Methods: This prospective, observational study involved emergency medicine (EM) residents with varying experience in guidewire visualization. Using an inanimate model, investigators placed guidewires randomly into the carotid artery or IJ vein. Residents, blinded to guidewire location, scanned the model and recorded their findings. The test performance of POCUS for arterially placed guidewires was evaluated through calculation of sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), and overall accuracy, using investigator placement as the non-reference standard.  Results: Twenty-five residents performed 51 observations. The test performance of POCUS for identifying arterially placed guidewires was sensitivity 95.0% (95%CI = 73.1-99.7%), specificity 96.8% (95%CI = 81.5-99.8%), NPV 96.8% (95%CI = 81.5-99.8%), and PPV 95.0% (95%CI = 73.1-99.7%). The overall accuracy was 96.1% (95%CI = 86.8-98.9%). Residents reported being very confident in their findings in 88.2% of all observations (95%CI = 76.6-94.5%), somewhat confident in 9.8% (95%CI = 4.3-21.0%), and not very confident in 2.0% (95%CI = 0.4-10.3%). No errors occurred among upper-level residents (post-graduate years 2-3) or those reporting >5 prior wire visualizations in live patients. Conclusions: This study is the first to demonstrate that physicians can easily identify misplaced guidewires located in the carotid artery with a high degree of accuracy using POCUS. We recommend routine scanning of the IJ vein and carotid artery prior to vessel dilation to reduce the likelihood of carotid artery injury.